2020
DOI: 10.1080/17843286.2020.1798668
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of COVID-19 and its comparison with influenza pneumonia

Abstract: Objectives: To recognise clinical features of COVID-19 pneumonia and its differences from influenza pneumonia. Methods: 246 patients were enrolled into COVID-19 cohort and 120 patients into influenza cohort. All data were collected and analysed retrospectively. The variables under focus included demographic, epidemiological, clinical, laboratory and imaging characteristics of COVID-19 pneumonia and comparison were made with influenza pneumonia. Results: The COVID-19 cohort included 53.25% female and 46.75% mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 27 publications
4
33
0
Order By: Relevance
“…The median age of COVID-19 patients in our study was lower than in recent multi-center cohort studies of patients hospitalized with SARS-CoV-2 infection in Germany that observed a mean age of 68-70 years 36,37 and with a recent cohort study analyzing electronic healthcare databases of the US Department of Veterans Affairs that observed a mean age of 69 years 19 . However, our observation that patients with SARS-CoV-2 infection are generally younger than seasonal influenza patients is consistent with previously published data 14,15,18 . Interestingly, among patients that were admitted to the ICU, age did not significantly differ between the two groups.…”
Section: Discussionsupporting
confidence: 93%
“…The median age of COVID-19 patients in our study was lower than in recent multi-center cohort studies of patients hospitalized with SARS-CoV-2 infection in Germany that observed a mean age of 68-70 years 36,37 and with a recent cohort study analyzing electronic healthcare databases of the US Department of Veterans Affairs that observed a mean age of 69 years 19 . However, our observation that patients with SARS-CoV-2 infection are generally younger than seasonal influenza patients is consistent with previously published data 14,15,18 . Interestingly, among patients that were admitted to the ICU, age did not significantly differ between the two groups.…”
Section: Discussionsupporting
confidence: 93%
“…Among laboratory findings, leukocytosis and leukopenia were predominant in patients with influenza-associated and COVID-19-associated pneumonia, respectively. This was in line with prior studies that reported frequently ob-served leukopenia and anosmia in patients with COVID-19 infection [22,26]. These findings suggest that a thorough review of the clinical presentations and laboratory findings of each patient could give diagnostic clues for differentiating COVID-19 and influenza among patients with respiratory symptoms.…”
Section: Discussionsupporting
confidence: 90%
“…Reviewing the literature we found few small -scale studies comparing laboratory parameters of adult patients with COVID- 19 and In uenza 32,42,43 and none compared with RSV. Only two studies investigated the NLR levels in COVID-19 compared to In uenza.…”
Section: Discussionmentioning
confidence: 99%